Evaluation of modulatory properties of Bacillus cereus isolated from the gut of Litopenaeus vannamai on growth, intestinal morphology, digestive enzyme activities, immune responses and disease resistance of Litopenaeus vannamai. (29th November 2020) - Li, Haidong; Fan, Shiliang; Gao, Yang; Cai, Yuyong; Chu, Zhangjie; Wang, Ling
Abstract: A 42‐day feeding trial was conducted to investigate the effects of supplementation with various additives from Bacillus cereus A4 (fermentation supernatant, FS; live cells, BC; spores, BS; and cell‐free extract, CE) on the growth performance, intestinal morphology, digestive enzyme activities, immune responses and disease resistance of Litopenaeus vannamei (initial weight approximately 2.34 g). The results indicated that the growth performance of shrimp in BC, BS and CE groups improved significantly and no significant difference was observed between the control and FS groups. The villus height of the shrimp mid‐intestine in the FS, BC, BS and CE groups improved significantly compared with the control, and the maximum intestinal wall thickness was observed in BS group. Compared to the control, the activities of amylase, trypsin, lipase, acid phosphatase (ACP), alkaline phosphatase (AKP), superoxide dismutase, lysozyme and total nitric oxide synthase and the relative expression levels of Immune deficiency (Imd), Toll and Relish genes in shrimp of BC, BS and CE groups enhanced significantly. The activities of amylase, trypsin, ACP, AKP and the relative expression levels of Imd, Toll and Relish genes in shrimp of BC and BS groups were significantly higher than those of other groups. In the challenge test against Vibrio parahaemolyticus, the cumulative mortality of shrimp in BC and BS groups was significantly lower compared with that of other groups. Thus, the live cells and spores of B. cereus A4 provided superior probiotic benefits to L. vannamei, including improvements in growth, intestinal morphology, digestive enzyme activities, disease resistance and immune responses.